Pertumbuhan ekonomi antar daerah di wilayah Ajatappareng dalam perspektif ekonomi Islam (Studi lima kabupaten di provinsi Sulawesi Selatan) - Usmayani, Ilham Putra; Ningsih, Restu Fitria; Pangestu, Dian Resky (AL-Muqayyad, 2024)
The Ajatappareng region in South Sulawesi is a strategic area within the Spatial Planning (RTRW) as part of the Parepare and surrounding key development zones. This study aims to analyze interregional economic growth using descriptive statistical methods based on secondary data from 2011–2015. Additionally, the Location Quotient (LQ) analysis was employed to identify key sectors in each district. The results indicate that the electricity and gas supply sector is the leading sector across all regions, followed by agriculture, forestry, and fisheries, which have significant potential to drive regional economic growth. From an Islamic economic perspective, regional development is guided by Sharia principles to achieve sustainable and stable growth.